EFFECTIVENESS OF INTERNAL AUDIT IN RURAL BANKS - Eti Kusmiati; Wahyuningsih Wahyuningsih (UNIB Press, 2022)
The purpose of this study is to assess the efficiency of internal audit implementation. This study takes a quantitative approach and employs a survey-descriptive method. A proportional stratified random sampling approach was used to pick respondents. A total of 59 persons were chosen from a total population of 110. Internal audit variables measured include independence, professional ability, the scope of work, implementation of inspection activities, and management of the internal audit department. Several steps of data analysis were completed. The instrument is initially tested for validity and reliability, after which the findings of the questionnaire are scored using a Likert scale. The categorizing of each response element is the final step. The results showed that the internal audit at PT BPR Intan West Java was carried out effectively, with the order of the highest to lowest scores being: Professional Ability, Implementation of Examination Activities, Scope of Work, Management of the Internal Audit Section, and Independence. Other findings indicate that the assessment of the effectiveness of the internal audit of PT BPR Intan West Java received positive opinions, both respondents from the elements of the Branch Head, Head of Section, and staff representatives.